2011
DOI: 10.14527/c1s3m1
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of class management strategies of preschool teachers in classroom activities

Abstract: ÖzetÖğretmenlerin sınıf yönetimi stratejileri, eğitim öğretim etkinliklerinin sağlıklı yürütülmesinde, çocukların akademik ve sosyal başarılarının artmasında ve çocukların yaşam becerileri kazanmasında önemli yer tutmaktadır. Bu araştırmanın amacı, okul öncesi öğretmenlerinin sınıf içi etkinliklerde kullandıkları sınıf yönetimi stratejilerinin gözlem yoluyla incelenmesidir. Araştırmanın çalışma grubunu, Ankara il merkezinde çalışan altı okul öncesi öğretmeni oluşturmaktadır. Okul öncesi öğretmenlerinin sınıf y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 8 publications
(3 reference statements)
0
16
0
4
Order By: Relevance
“…Başçı and Dilekmen (2009) argue that most of the elementary school teachers try to establish discipline in the classroom through physical punishment. Many studies in the literature also show that teachers are verbally warned children by using the first type of punishment against undesirable behavior (Akgün, Yarar & Dinçer, 2011;Dobbs-Oates, Arnold, & Doctoroff, 2004;Günay, 2005;Sadık, 2004). Another striking finding of the present study is the difference between the opinions of the teacher and the children regarding the behaviors of the teacher when the class rules are not followed.…”
Section: Discussionmentioning
confidence: 99%
“…Başçı and Dilekmen (2009) argue that most of the elementary school teachers try to establish discipline in the classroom through physical punishment. Many studies in the literature also show that teachers are verbally warned children by using the first type of punishment against undesirable behavior (Akgün, Yarar & Dinçer, 2011;Dobbs-Oates, Arnold, & Doctoroff, 2004;Günay, 2005;Sadık, 2004). Another striking finding of the present study is the difference between the opinions of the teacher and the children regarding the behaviors of the teacher when the class rules are not followed.…”
Section: Discussionmentioning
confidence: 99%
“…Bu doğrultuda eğitimlerinin son yılına gelen öğretmen adaylarının sınıf yönetiminde zorluk çekmelerinin nedeni, bugüne kadar uygulamaya yönelik derslerinin yeterli gelmemesi olabilir. Buna ek olarak, sınıf yönetimi alan yazınına bakıldığında sınıfta bireyler arası sağlanan olumlu ilişki, öğretmenin sözel olmayan davranışları, çocukların davranışlarının düzenlenmesi, sınıfta uyulması gereken kuralların belirlenmesi, zaman yönetimi ve iletişim gibi becerilerin de sınıf yönetimini sağlamada kritik bir öneme sahip olduğu söylenmektedir (Akgün, Yarar ve Dinçer, 2011;Bulut, 2008;Celep, 2004;Ekici, 2004;Erden, 2005;Şeker, 2000). Ancak yukarıda bahsi geçen sınıf yönetimi becerilerinin öğretmenlik tecrübesi ile doğru orantılı olarak geliştiği de alan yazındaki çalışmaların bulguları arasında göze çarpmaktadır (Dinçer ve Akgün, 2015;O'Brien ve Goddard, 2006;Yeşilyurt ve Çankaya, 2008).…”
Section: Sonuç Ve Tartışmaunclassified
“…In a study conducted in Turkey sample (Buyuktaskapu Soydan et al, 2018), it was emphasized that the majority of the preschool teachers adopt controller discipline and discipline based on obedience against the problem behaviors. The study by Akgün, Yarar, & Dincer (2011) based on the supervision performed by preschool teachers in classroom environment showed that teachers practice the negative classroom management strategies more. Since adopting such a discipline understanding against the behaviors of the children has an impact on highlighting the characteristics such as shyness, introversion, and timidity, there is a need for the efforts to improve the strategies and approaches in this scope.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%